Spatio-Temporal Assessment of Atmospheric Pollution (Aerosols, Black Carbon) and Snow Cover Dynamics in Himachal Pradesh Using Sentinel Data - Vyas, Pratyush (My University, 2025)
The mountainous Indian state of Himachal Pradesh, located in the western Himalayas, is becoming more and more vulnerable to climate change, particularly with regard to its Cryospheric systems and snow cover. In this area, snow and ice are essential for maintaining perennial rivers as well as controlling biological balance and producing electricity. Anthropogenic activities have increased atmospheric aerosols and black carbon levels in recent years, which are known to speed up snowmelt by changing surface albedo and regional radiative forcing. Using three primary indicators—the Aerosol Index (AI), Black Carbon (BC), and Normalized Difference Snow Index (NDSI)—this thesis examines the spatiotemporal variability of snow cover and air pollution throughout Himachal Pradesh in 2020, 2022, and 2024. Sentinel-5P data was used to estimate AI and BC, while Sentinel-2 imagery was used to compute NDSI, which provides high spatial resolution information on the extent of seasonal snow cover. Google Earth Engine (GEE) was used to process and analyse all datasets, and maps, statistical charts, and seasonal composite pictures were used to display the findings. The choice of 2020 as a baseline year, when emissions were much lower because of the worldwide COVID-19 lockdown, is a novel feature of this study. This offers a natural control setting for analysing the effects of pollution and environmental recovery in later years. Four major seasons were examined: Winter (October–February), Spring (February–April), Summer (May – June), and Monsoon (July–September). The findings show that, especially in the spring and summer, there is a constant negative correlation between NDSI values and atmospheric pollution levels (AI and BC). While 2022 and 2024 showed decreased NDSI and increased black carbon deposition, indicating rapid melting, 2020 had the maximum snow cover. This study demonstrates that air pollutants are a major contributor to the Himalayan cryosphere's deterioration. Recommendations for community- level monitoring, renewable energy transitions, and pollution management have also been proposed. The combined use of Sentinel-2 and Sentinel-5P demonstrates the effectiveness of multi-sensor satellite measurements in directing policy and climate adaptation in high-altitude areas.
Keywords: Black Carbon Deposition; Normalized Difference Snow Index (NDSI); Sentinel Satellite Remote Sensing; Western Himalayas Climate Impact